Gender-sensitive bioetichs in medicine: basics and challenges - Figueroa, Gustavo (Acta Bioethica, 2017)
The emerging character of bioethics did not encourage the attempts to develop a gender-sensitive bioethics. What is at stake is the possibility and urgency of answering three interrelated questions: fundamentals and basic concepts of gender identity, the state of the contributions offered by bioethics of delimiting two different but interconected leves of moral dilemmas: the feminine level and the masculine level, and to sketch an anthropological based general approach to a feminine-sensitive bioethics.